O impacto da inovação aberta outbound em empresas brasileiras - Rosa, Priscila Luiz (2017)
Open innovation is an emerging theme that has been gaining prominence on the part of scholars and organizations, and can be done from two perspectives: inbound and outbound, which respectively refer to the internal use of external knowledge, and the external use of internal knowledge. However, there is a need for more empirical studies aimed at the outbound perspective, since research in this area remains neglected. For the development of this work will be carried out a qualitative and quantitative exploratory applied research to investigate the influence of open outbound innovation on the performance of Brazilian organizations. This work is structured in the form of 3 articles, aimed at achieving the general objective of the research. In the first article we present a systematic bibliometric review, addressing a comprehensive view on open outbound innovation. This article presents practical aspects about the subject, offering organizations indications about the contribution of open outbound innovation to the improvement of organizational performance and the risks involved in the use of their practices through the panorama of current research. In the second article, we try to validate a set of factors to measure outbound open innovation practices in Brazilian technology-based organizations based on cluster and factorial analysis. From the cluster was carried out the grouping of respondent companies according to the results of using open innovation practices. Already with the aid of the factorial analysis was defined and validated a set of factors used to define the central characteristics of each group. The accomplishment of this article contributes to determine the distinct characteristics of companies that make use of open outbound innovation. In the third article, we investigate which factors discriminate the use of outbound open innovation practices in small and medium-sized technology-based companies. For this, we performed the statistical technique of discriminant analysis, which allowed us to identify that the main factor that discriminated the open innovation practices of small and medium enterprises is related to the possibility of these companies to create innovations based on technologies different from those that they have in their companies. The risk of loss of strategic knowledge from the dissemination of knowledge is considered one of the most common problems in open innovation.Considering the whole study carried out in this dissertation, it is observed that research on the contribution of the external use of internal knowledge to innovate (outbound) is apparently more complex and less frequent, but allows to complete the optics of analysis of open innovation in organizations. From the composition of the three articles, the paper concludes that once open innovation activities are effectively managed, the opening of the innovation process can positively affect the success of the innovation and consequently the financial performance of the organizations.